Catalyst for producing hydrogen, its production method, and hydrogen production method

A cost-effective and resource-efficient hydrogen production catalyst using ferromagnetic cobalt-iron alloy nanocrystals in a tungsten carbide lattice addresses the inefficiencies of platinum-based systems, achieving stable and high-efficiency hydrogen production from ammonia borane.

JP7659754B1Active Publication Date: 2025-04-10UNIV OF HYOGO +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2024036284
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2024-03-08
Publication Date
2025-04-10
Estimated Expiration
2044-03-08

AI Technical Summary

Technical Problem

Conventional hydrogen production methods using platinum catalysts are costly, resource-intensive, and inefficient for generating hydrogen from hydrogen-rich compounds like ammonia borane, especially for applications requiring stable and high-efficiency hydrogen production.

Method used

A hydrogen production catalyst composed of ferromagnetic cobalt-iron alloy nanocrystals dissolved in a lattice of tungsten carbide, which is more cost-effective and resource-abundant compared to platinum, and is designed to enhance the efficiency and stability of hydrogen production from ammonia borane.

Benefits of technology

The proposed catalyst achieves hydrogen production efficiency comparable to or exceeding that of platinum-based catalysts, while being more cost-effective and resource-efficient, and contributes to the miniaturization of fuel cells by stabilizing hydrogen gas production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007659754000001_ABST
    Figure 0007659754000001_ABST
Patent Text Reader

Abstract

Hydrogen gas (H2(g)) is produced stably and efficiently from ammonia borane (NH3BH3). [Solution] This catalyst for generating hydrogen from NH3BH3 is made of ferromagnetic tungsten carbide, in which Co-Fe alloy nanocrystals are dissolved in the lattice of tungsten carbide (WC). Tungsten carbide is mixed with an aqueous solution of NH3BH3, and NH3BH3 is hydrolyzed. At this time, NH3BH3 is adsorbed on the surface of WC, which is then cleaved to release protons (H + ) is released. + ) and the electron spins from the Co-Fe alloy nanocrystals, resulting in the magnetic dipole interaction between the protons (H + ) is accumulated and reduced to generate hydrogen molecules (H2). The magnetic repulsive interaction between the Co-Fe alloy nanocrystals and the diamagnetic hydrogen molecules (H2) results in a time derivative (d 2 Sirr / dt 2 ) vibrations caused by changes over time are suppressed, ensuring stable hydrogen generation.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a catalyst for producing hydrogen and a method for producing the same, and further to a method for producing hydrogen using the catalyst for producing hydrogen. [Background technology]

[0002] 2. Description of the Related Art Hydrogen has traditionally been attracting attention as an energy source that reduces environmental damage, and fuel cells that use hydrogen as fuel have been attracting attention and are being put to practical use.

[0003] Hydrogen is in a gas phase under normal temperature and pressure conditions, and the volume of a given reaction volume is several hundred to a thousand times that of the solid phase, and it is explosive, so it is difficult to store a large amount safely.To solve these problems with hydrogen gas and enable safe and easy handling, hydrogen gas obtained by reforming natural gas, methanol, gasoline, etc. is used as fuel for fuel cells.

[0004] This type of fuel not only has safety problems, but also does not generate sufficient electromotive force when used as fuel for fuel cells, making it impossible to realize sufficient performance as a power supply source.

[0005] In view of the problems with conventional hydrogen-containing media, extensive research has been conducted into fuels that are safe, easy to handle, and capable of generating sufficient electromotive force when used as fuel for fuel cells. As this type of fuel, ammonia borane (NH3BH3) has been proposed as a hydrogen-containing compound that contains hydrogen at a high concentration (Patent Documents 1 and 2).

[0006] The hydrogen contained in ammonia borane (NH3BH3) is produced by adding platinum (Pt) as a catalyst to an aqueous solution in which ammonia borane (NH3BH3) is dissolved and hydrolyzing the aqueous solution.

[0007] Conventionally, precious metals such as platinum (Pt) used as catalysts are scarce and expensive, making it difficult to generate hydrogen from ammonia borane (NH3BH3) at low cost and in a stable manner. Therefore, the applicant of the present application has proposed a catalyst that can replace precious metals such as platinum (Pt) (Patent Documents 3 and 4). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] JP 2006-286549 A [Patent Document 2] JP 2009-176556 A [Patent Document 3] JP 2023-61564 A [Patent Document 4] Patent No. 7417026 Summary of the Invention [Problem to be solved by the invention]

[0009] Incidentally, in fuel cells used as a driving source for mobile devices such as automobiles, and in fuel cells used as a power source for consumer portable terminal devices, it is desirable to generate hydrogen inexpensively, stably, and efficiently from hydrogen-containing compounds that store hydrogen at high concentrations, and further to realize a compact battery itself. [Means for solving the problem]

[0010] The inventors have focused on the catalytic action and function of platinum (Pt), which is used in producing hydrogen from hydrogen-containing compounds, particularly ammonia borane (NH3BH3), and have conducted extensive research, resulting in the realization of a hydrogen production catalyst that can achieve catalytic action equivalent to or greater than that of platinum (Pt).

[0011] In particular, the inventors have intensively studied the characteristics of platinum (Pt) used as a catalyst, and as a result, have focused on the fact that platinum (Pt) has magnetic properties, and have completed a hydrogen production catalyst that is less expensive than platinum (Pt) and can be obtained or supplied stably.

[0012] The hydrogen production catalyst proposed here is a catalyst that can be used in place of platinum (Pt), and is characterized by consisting of tungsten carbide (WC) in which ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals are dissolved in a solid solution within the lattice of tungsten carbide, and which has been made ferromagnetic by the application of an internal magnetic field. The tungsten carbide that constitutes this catalyst is characterized by having an internal magnetic field imparted thereto by encapsulating cobalt-iron (Co-Fe) alloy nanocrystals composed of 99.5 to 91.5 mol % of ferromagnetic cobalt (Co) and 0.5 to 8.5 mol % of iron (Fe).

[0013] The tungsten carbide used as the proposed hydrogen production catalyst is desirably a fine powder with a particle size of 32 μm or less in order to stably generate hydrogen (H2).

[0014] The tungsten carbide that constitutes the hydrogen production catalyst used to generate hydrogen (H2) from ammonia borane (NH3BH3) is manufactured through the following process.

[0015] First, a mixed aqueous solution is prepared by mixing a tungsten component with a ferromagnetic cobalt component and an iron component, then the mixed aqueous solution is evaporated to dryness or spray-dried to prepare a solid material containing cobalt and iron components, the solid material is thermally decomposed to produce an oxide powder, and the solid material is further reduced by hydrogen heat to produce a cobalt-iron (Co-Fe) alloy solid solution tungsten alloy powder.

[0016] The cobalt-iron (Co-Fe) alloy solid solution tungsten alloy powder is then carbonized to produce tungsten carbide that encapsulates ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals and is made ferromagnetic by the application of an internal magnetic field.

[0017] In the process of carbonizing the cobalt-iron (Co-Fe) alloy solid solution tungsten alloy powder, tungsten complex carbides (W6(Co-Fe)6C, (Co-Fe)2W4C) are produced along with tungsten carbide that contains ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals and is made ferromagnetic by the application of an internal magnetic field.

[0018] The mixed aqueous solution used to produce the tungsten carbide is a mixture of a cobalt-iron (Co-Fe) alloy component, which is a mixture of cobalt (Co) at a ratio of 99.5 to 91.5 mol % and iron (Fe) at a ratio of 0.5 to 8.5 mol %, and a tungsten component at a molar ratio of 20:80.

[0019] The tungsten carbide functioning as a catalyst and having the above-mentioned structure is mixed with an aqueous solution of ammonia borane (NH3BH3) dissolved therein. The aqueous solution of ammonia borane (NH3BH3) mixed with tungsten carbide is hydrolyzed, so that the tungsten carbide functions as a catalyst to generate hydrogen gas (H2(g)) from ammonia borane (NH3BH3).

[0020] When generating hydrogen gas from ammonia borane (NH3BH3) by hydrolysis of an aqueous solution containing dissolved ammonia borane mixed with tungsten carbide, which functions as a catalyst, the repulsive interaction between the diamagnetic hydrogen gas and the ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals encapsulated in the tungsten carbide causes the hydrogen gas (H2(g)) to desorb from the surface of the tungsten carbide.

[0021] When producing hydrogen (H2) from ammonia borane (NH3BH3) using the above-mentioned hydrogen production catalyst made of tungsten carbide, an aqueous solution is prepared by mixing tungsten carbide with an aqueous solution in which ammonia borane (NH3BH3) is dissolved. When this aqueous solution is hydrolyzed, ammonia borane (NH3BH3) is adsorbed and cleaved on the surface of tungsten carbide (WC) that constitutes the tungsten carbide that functions as a catalyst, and protons (H +) is released. The proton (H + ) and the electron spins from the ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals encapsulated in tungsten carbide, causing protons (H + ) and reduce it to generate diamagnetic hydrogen molecules (H2). Here, the time derivative (d 2 Sirr / dt 2 The unstable oscillation of the time-dependent changes in the cobalt-iron (Co-Fe) alloy nanocrystal surface is suppressed, and hydrogen molecules (H2) are desorbed from the surface to generate hydrogen gas (H2(g)). Effect of the Invention

[0022] The tungsten carbide proposed here, which encapsulates cobalt-iron (Co-Fe) alloy nanocrystals and is subjected to an internal magnetic field, is hydrophilic and therefore suitable for use as a catalyst in the hydrolysis of ammonia borane (NH3BH3), a hydrogen-containing compound that enables high-concentration hydrogen storage.

[0023] This hydrogen production catalyst using tungsten carbide enables the highly efficient production of hydrogen gas (H2(g)) from the hydrogen-containing compound ammonia borane (NH3BH3). In particular, the efficiency of hydrogen gas (H2(g)) production is equal to or even exceeds that achieved when platinum (Pt) is used as a catalyst.

[0024] Furthermore, hydrogen production catalysts using tungsten carbide improve the conversion rate of hydrogen gas (H2(g)) produced by hydrolysis of ammonia borane (NH3BH3), enabling stable and highly efficient production of hydrogen gas (H2(g)), and can also contribute to the realization of smaller fuel cells themselves.

[0025] The catalyst using tungsten carbide mentioned above does not use precious metals such as platinum (Pt), but uses a material that is an abundant resource with no risk of depletion, so it can be supplied cheaply and stably.

[0026] In addition, the proposed catalyst reduces the time derivative (dSirr / dt) of the entropy production rate of the irreversible process that produces hydrogen gas (H2(g)). 2 Sirr / dt 2 This suppresses unstable oscillations in the time-dependent changes of hydrogen (H2), enabling stable production of hydrogen (H2).

[0027] The magnetic repulsive interaction between ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals and diamagnetic hydrogen molecules (H2) enables rapid desorption of hydrogen molecules (H2) from the surface of the cobalt-iron (Co-Fe) alloy nanocrystals, enabling highly efficient hydrogen production. [Brief description of the drawings]

[0028] [Figure 1] FIG. 1 is a schematic diagram showing a mechanism for producing hydrogen (H2) by hydrolysis of ammonia borane (NH3BH3) using the tungsten carbide according to the present invention as a catalyst. [Diagram 2] FIG. 2 is a diagram showing an energy dispersive X-ray spectroscopy (EDX) image of tungsten carbide encapsulated in a nanocrystalline phase of a cobalt-iron (Co-Fe) alloy produced in this example. [Diagram 3] This is a characteristic diagram showing the change over time in the amount of hydrogen gas generated from ammonia borane (NH3BH3) using the tungsten carbide of this embodiment, a reference catalyst (Pt-NPsBall) distributed by the Catalysis Society of Japan, which is made by supporting platinum (Pt) nanoparticles on alumina nanoparticles and forming them into granules, and a catalyst (Pt-NPs) made by finely crushing this catalyst. [Figure 4]FIG. 13 is a graph showing the change over time in the time derivative (dSirr / dt) of entropy generation in an irreversible process in a hydrogen production reaction when the tungsten carbide according to the present embodiment and Pt-NPs (Ball), Pt-NPs (1), and Pt-NPs (2) shown as comparative examples are used as catalysts. [Diagram 5] FIG. 13 is a graph showing the change over time in the second time derivative (dSirr / dt) of entropy generation in the irreversible process in the hydrogen production reaction when the tungsten carbide of this embodiment is used as a catalyst. [Figure 6] FIG. 13 is a graph showing the change over time in the second-order time derivative (dSirr / dt) of entropy generation in the irreversible process in the hydrogen production reaction when Pt-NPs (Ball), Pt-NPs (1), and Pt-NPs (2) shown as comparative examples were used as catalysts. [Figure 7] This is a schematic diagram showing the mechanism by which hydrogen molecules (H2) produced by hydrolysis of ammonia borane (NH3BH3) are released as gaseous hydrogen gas. [Figure 8] FIG. 1 is a schematic diagram showing the mechanism of hydrogen (H2) production when ammonia borane (NH3BH3) is hydrolyzed using platinum (Pt) as a catalyst. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. The present embodiment described below is a catalyst for hydrogen production used to generate hydrogen (H2) from ammonia borane (NH3BH3), which is a hydrogen-containing compound. This catalyst is made of tungsten carbide that contains a cobalt-iron (Co-Fe) alloy nanocrystalline phase and is given magnetic properties. This tungsten carbide is a tungsten carbide in which ferromagnetic cobalt (Co) and iron (Fe) are forcedly dissolved in a non-equilibrium solid solution in a tungsten carbide (WC) lattice. Cobalt (Co) and Iron (Fe) It is made by carbonizing solid-solution tungsten alloy powder.

[0030] The cobalt (Co) and iron (Fe) solid solution tungsten alloy powder used for making the tungsten carbide of this embodiment is made by mixing the aqueous solution of ammonium tungstate containing tungsten ions with the aqueous solution of cobalt acetate containing cobalt ions and the aqueous solution of iron nitrate containing iron ions.

[0031] This mixed aqueous solution is preferably a mixture of a cobalt-iron (Co-Fe) alloy component, which is a mixture of 99.5 to 91.5 mol % cobalt (Co) and 0.5 to 8.5 mol % iron (Fe), and a tungsten component in a molar ratio of 20:80.

[0032] The above-mentioned mixed aqueous solution is evaporated to dryness or spray-dried to produce a dried product. The dried product obtained here is thermally decomposed into oxides. The thermal decomposition of the dried product into oxides is carried out by holding it in an oxygen atmosphere at 500°C to 600°C, preferably at 570°C, for about 2 hours.

[0033] The oxide produced by pyrolyzing the dried product is reduced with hydrogen to obtain a tungsten oxide powder dissolved with cobalt (Co) and iron (Fe). This hydrogen reduction is performed by holding the oxide obtained in the above-mentioned process in a hydrogen atmosphere at 750°C to 850°C, preferably in a hydrogen atmosphere at 800°C, for about 3 hours. The oxide is reduced with hydrogen to obtain a tungsten alloy powder dissolved with cobalt (Co) and iron (Fe).

[0034] The cobalt (Co) and iron (Fe) solid solution tungsten alloy powder produced here is a non-equilibrium forced solid solution of cobalt (Co) and iron (Fe) in the tungsten (W) lattice.

[0035] The cobalt (Co) and iron (Fe) solid-solution tungsten alloy powder prepared as described above is carbonized to form tungsten carbide containing a cobalt-iron (Co-Fe) alloy nanocrystalline phase and having an internal magnetic field applied thereto. This tungsten carbide having an internal magnetic field applied thereto is used as a catalyst for hydrogen production, which is used to generate hydrogen (H2) from ammonia borane (NH3BH3), a hydrogen-containing compound.

[0036] The carbonization process of the cobalt (Co) and iron (Fe) solid-solution tungsten alloy powder is carried out by heating in a carbon dioxide (CO2) gas atmosphere. For example, after the cobalt (Co) and iron (Fe) solid-solution tungsten alloy powder is placed in a reactor, CO2 gas is introduced into the reactor, and the reactor is heated to an atmosphere of about 900°C for about 20 hours.

[0037] However, in the case of cobalt (Co) and iron (Fe) solid solution tungsten alloy powder, if the content ratio of cobalt (Co) and iron (Fe) relative to tungsten (W) is excessive, carbonization is inhibited, and it is difficult to produce tungsten carbide containing a cobalt-iron (Co-Fe) alloy nanocrystalline phase. In the above-mentioned mixed aqueous solution state, if the total of the cobalt (Co) component and the iron (Fe) component exceeds 30 mol%, carbonization is inhibited, and it is not possible to produce tungsten carbide containing a cobalt-iron (Co-Fe) alloy nanocrystalline phase.

[0038] In addition, when the ferromagnetic cobalt (Co) and iron (Fe) components are less than 1 mol% in the mixed aqueous solution, the proportion of the cobalt (Co) and iron (Fe) components dissolved in the tungsten carbide is insufficient, and high catalytic activity cannot be obtained. This is thought to be because the magnetization of the tungsten carbide containing the cobalt-iron (Co-Fe) alloy nanocrystalline phase is insufficient, and catalytic properties utilizing magnetism cannot be obtained. Therefore, it is insufficient to be used as a catalyst for hydrogen production, which is used to generate hydrogen (H2) from ammonia borane (NH3BH3).

[0039] Therefore, a mixed aqueous solution of a cobalt-iron (Co-Fe) alloy component, which is a mixture of cobalt (Co) in a ratio of 99.5 to 91.5 mol% and iron (Fe) in a ratio of 0.5 to 8.5 mol%, and a tungsten (W) component in a molar ratio of 20:80, is used as a starting material.

[0040] This tungsten carbide has a structure in which ferromagnetic cobalt-iron (Co-Fe) nanocrystals are contained within a tungsten carbide (WC) skeleton. Cobalt-iron (Co-Fe) nanocrystals are crystalline bodies having a structure in which cobalt (Co) and iron (Fe) atoms are crystallized, and are polycrystalline bodies having grain sizes of several nm to several tens of nm.

[0041] The tungsten carbide according to the present embodiment used as a catalyst for hydrogen production is preferably crushed, for example, to a particle size of 32 μm or less, in order to form a mixed aqueous solution in which it is uniformly mixed with an aqueous solution of ammonia borane (NH3BH3).

[0042] The tungsten carbide according to the present embodiment, which is manufactured through the above-mentioned process, contains a ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystalline phase in the skeleton of tungsten carbide (WC), and exhibits ferromagnetism with a hysteresis loop in the magnetic field-magnetization curve. The ferromagnetic tungsten carbide realizes high catalytic activity and effectively functions as a hydrogen production catalyst used to generate hydrogen (H2) from ammonia borane (NH3BH3).

[0043] To generate hydrogen (H2) from ammonia borane (NH3BH3) using the above-mentioned tungsten carbide as a catalyst, a mixture of this tungsten carbide and water is mixed with an aqueous solution of ammonia borane in which crystalline ammonia borane (NH3BH3) is dissolved. When the aqueous solution of ammonia borane mixed with this tungsten carbide is hydrolyzed, hydrogen gas (H2(g)) gas is generated according to the following formula (1).

[0044] NH3BH3+2H2O=NH4 + +BO2- +3H2···(1)

[0045] The aqueous solution of ammonia borane (NH3BH3) may be prepared by directly adding ammonia borane to the mixture containing tungsten carbide and dissolving it therein.

[0046] Tungsten carbide encapsulating a nanocrystalline cobalt-iron (Co-Fe) alloy phase acts as a catalyst in the hydrolysis of aqueous solutions of ammonia borane (NH3BH3) and promotes the production of hydrogen (H2) from NH3BH3.

[0047] Here, the mechanism by which the above-mentioned tungsten carbide functions as a catalyst when ammonia borane (NH3BH3) is hydrolyzed to generate hydrogen (H2) will be described with reference to FIG.

[0048] When an aqueous solution (NH3BH3(aq)) in which the crystalline solid ammonia borane (NH3BH3(cr)) is dissolved is mixed with an aqueous solution in which tungsten carbide containing a cobalt-iron (Co-Fe) alloy nanocrystalline phase is immersed, the ammonia borane (NH3BH3) molecules are attracted into the WC skeleton by the attractive interaction of the WB bonds. Then, the BN bonds, which are the bonds between boron (B) and nitrogen (N) that make up ammonia borane (NH3BH3), are broken, and the stable molecule NH3(aq) and the unstable molecule BH3(aq) are generated. At this time, protons (H + ) is generated. The protons (H + The nuclear spins of the cobalt (Co) align to cancel out the electronic spins of the cobalt (Co), producing hydrogen gas (H2(g)). Hydrogen gas (H2(g)) is diamagnetic, and therefore interacts repulsively with the ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystalline phase. As a result, the time derivative (dSirr / dt) of the entropy production rate of the irreversible process that produces hydrogen gas (H2(g)) is 2 Sirr / dt 2This suppresses unstable oscillations in the time-dependent changes of hydrogen gas (H2(g)), enabling the stable generation of hydrogen gas (H2(g)). Furthermore, rapid desorption of hydrogen molecules (H2) from the surface of the cobalt-iron (Co-Fe) alloy nanocrystals is achieved, making it possible to produce hydrogen (H2) with high efficiency. EXAMPLES

[0049] Next, specific examples of the catalyst for producing hydrogen according to the present invention will be described. In this embodiment, tungsten carbide containing a cobalt-iron (Co-Fe) alloy nanocrystalline phase used as a catalyst for hydrogen production is produced by carbonizing a tungsten alloy powder containing cobalt (Co) and iron (Fe). The tungsten alloy powder containing cobalt (Co) and iron (Fe) is produced by using a mixed aqueous solution obtained by mixing an aqueous solution of ammonium tungstate containing tungsten ions with an aqueous solution of cobalt acetate containing cobalt ions and an aqueous solution of iron nitrate containing iron ions. This mixed aqueous solution was produced by mixing an aqueous solution of ammonium tungstate with an aqueous solution of cobalt acetate and iron nitrate. Here, the mixed aqueous solution was produced by mixing an aqueous solution of ammonium tungstate with an aqueous solution of cobalt acetate and iron nitrate so that the molar ratio of the cobalt-iron (Co-Fe) alloy component, which is mixed at a ratio of 92 mol% cobalt (Co) and 8 mol% iron (Fe), and the tungsten component was 20:80.

[0050] This mixed aqueous solution is evaporated to dryness to produce a dried product. This dried product is then held in an oxygen atmosphere at 570°C for two hours to be thermally decomposed into oxides. The thermally decomposed oxides are then held in a hydrogen atmosphere at 800°C for three hours to be reduced with hydrogen. This oxide is reduced with hydrogen to produce a cobalt-iron (Co-Fe) solid solution tungsten alloy powder in which cobalt is forced into a non-equilibrium solid solution.

[0051] 1 g of the obtained cobalt-doped tungsten alloy powder was placed in a reactor, carbonized by flowing carbon dioxide (CO2) gas into the reactor and heating the reactor to 900°C and holding the temperature for 24 hours.

[0052] When carrying out this carbonization process, since it is not possible to directly carbonize using CO2 gas, a compressed compact of Al-Fe alloy powder was placed in advance in the reactor, and this compact was carbonized as an agent for converting CO2 gas into carbon monoxide (CO) gas.

[0053] The cobalt and iron-dissolved tungsten alloy powder carbonized through the above-mentioned treatment process is treated as tungsten carbide containing a cobalt-iron (Co-Fe) alloy nanocrystalline phase. An energy dispersive X-ray spectroscopy (EDX) image of this tungsten carbide containing a cobalt-iron (Co-Fe) alloy nanocrystalline phase is shown in Figure 2.

[0054] That is, in FIG. 2, Area#1 is a cobalt-iron (Co-Fe) alloy nanocrystalline phase (92Co-8Fe) with a molar ratio of cobalt (Co) and iron (Fe) of 92:8. Area#2 is a tungsten carbide (WC) skeleton. Area#3 is a region where tungsten complex carbides (W6(Co-Fe)6C and (Co-Fe)2W4C) are mixed. Area#4 is a tungsten carbide (WC) skeleton like Area#2.

[0055] The obtained Co-WC solid solution phase-encapsulated tungsten carbide was used as a catalyst to produce hydrogen gas (H2(g)) from ammonia borane (NH3BH3) through the process shown below.

[0056] First, the powder of tungsten carbide encapsulated in a nanocrystalline phase of a cobalt-iron (Co-Fe) alloy produced through the above process was mixed with pure water to prepare a mixed liquid. This mixed liquid was produced by weighing out 20 mg of tungsten carbide encapsulated in a nanocrystalline phase of a cobalt-iron (Co-Fe) alloy with a particle size of 32 μm or less, adding it to 1 ml of pure water, and stirring it with a stirrer.

[0057] Here, the tungsten carbide containing the nanocrystalline phase of cobalt-iron (Co-Fe) alloy was crushed to a fine powder and classified to have a particle size of 32 μm or less. Hereinafter, the tungsten carbide containing the nanocrystalline phase of cobalt-iron (Co-Fe) alloy will be abbreviated as WC-(Co0.92-Fe0.08) carbide.

[0058] Next, 1.5 ml of 0.5 mmol of ammonia borane (NH3BH3) powder was mixed with 1.5 ml of pure water to prepare an ammonia borane aqueous solution.

[0059] The mixture of tungsten carbide (WC-(Co0.92-Fe0.08) carbide) prepared as described above was mixed with an aqueous solution of ammonia borane to hydrolyze ammonia borane (NH3BH3).

[0060] The amount of hydrogen gas (H2(g)) generated during this hydrolysis process was measured by volume (HEV) and converted to molar amount. The amount of hydrogen gas (H2(g)) generated was evaluated by time change to evaluate the rate of hydrogen evolution reaction (HER). The amount of hydrogen gas (H2(g)) generated was measured at a temperature of 308K. The measurement results are shown in A in Figure 3.

[0061] Here, the measured value of the change over time in the amount of hydrogen gas (H2(g)) generated shown in Figure 3 was the average value of four measurements carried out to evaluate reusability. That is, after the first measurement of the amount of hydrogen gas (H2(g)) generated was completed, the ammonia borane solution was drained from the aqueous solution for hydrolysis, and then the second ammonia borane solution was poured in and the amount of hydrogen gas (H2(g)) generated was measured again. After that was completed, the ammonia borane solution was similarly drained from the aqueous solution for hydrolysis, and then the third ammonia borane solution was poured in and the amount of hydrogen gas (H2(g)) generated was measured again, and after that was completed, the ammonia borane solution was drained from the aqueous solution for hydrolysis. This measurement was repeated three times, and after the measurement, the tungsten carbide (WC-(Co0.92-Fe0.08) carbide) used as a catalyst was taken out of the aqueous solution for hydrolysis and exposed to the air for 24 hours. The tungsten carbide mixture thus extracted was mixed with an aqueous solution of ammonia borane to prepare an aqueous solution, which was then hydrolyzed and the amount of hydrogen gas (H2(g)) generated was measured for the fourth time.

[0062] Here, the production ability of hydrogen gas (H2(g)) from ammonia borane (NH3BH3) was compared when the tungsten carbide (WC-(Co0.92-Fe0.08) carbide) according to this embodiment was used as a catalyst and when a platinum (Pt)-based precious metal was used as a catalyst.

[0063] As catalysts for comparison, a reference catalyst (Pt-NPs(Ball)) distributed by the Catalysis Society of Japan, which is made by supporting platinum (Pt) nanoparticles on alumina nanoparticles and molding them into granules, and a catalyst (Pt-NPs(1)) made by finely crushing the reference catalyst, were prepared. Experiments on hydrogen gas (H2(g)) production using these catalysts listed as comparative examples were also conducted four times in order to compare with the case of using tungsten carbide (WC-(Co0.92-Fe0.08)carbide) of this embodiment.

[0064] When Pt-NPs (Ball) and Pt-NPs (1) are used as catalysts as comparative examples, these catalysts are mixed with pure water to prepare mixed water, similar to the case of using WC-(Co0.92-Fe0.08) carbide in this embodiment. These mixed waters are prepared by adding 20 mg of powder of Pt-NPs (Ball) and Pt-NPs (1) to 1 ml of pure water and stirring with a stirrer.

[0065] Incidentally, Pt-NPs(1), which is made by finely grinding granular Pt-NPs(Ball), was discharged from the mixed aqueous solution together with the wastewater of the aqueous ammonia borane (NH3BH3) solution, which was conducted every time an experiment was conducted to generate hydrogen gas (H2(g)) by hydrolysis, and a decrease in the amount of hydrogen gas (H2(g)) generated was observed. Therefore, when Pt-NPs is used as a catalyst, in order to clarify the inherent catalytic action of platinum (Pt), new finely ground granular Pt-NPs(Ball) was used every time the amount of hydrogen gas (H2(g)) generated was measured four times. This is referred to as Pt-NPs(2). This new ground Pt-NPs(2) was also mixed with pure water every time it was used as a catalyst, and used as the mixed water. This mixed water was also prepared by putting 20 mg of Pt-NPs(2) powder into 1 ml of pure water and stirring it with a stirrer.

[0066] Then, in order to hydrolyze ammonia borane (NH3BH3), ammonia borane (NH3BH3) powder is mixed with pure water to prepare an ammonia borane (NH3BH3) aqueous solution. This aqueous solution was prepared by mixing 1.5 ml of 0.5 mmol of ammonia borane (NH3BH3) powder with 1.5 ml of pure water.

[0067] Then, the mixtures of the aforementioned Pt-NPs (Ball), Pt-NPs (1), and Pt-NPs (2) were mixed with an aqueous solution of ammonia borane to hydrolyze ammonia borane (NH3BH3).

[0068] The amount of hydrogen gas (H2(g)) generated in this hydrolysis process was measured by volume (HEV) and converted to molar amount. The amount of hydrogen gas (H2(g)) generated was evaluated by changing with time to evaluate the hydrogen evolution reaction (HER) rate. The amount of hydrogen gas (H2(g)) generated was measured at a temperature of 308K. The measurement results are shown in Figure 3. The measurement results when Pt-NPs (Ball) was used as a catalyst are shown in B in Figure 3. The measurement results when Pt-NPs (1) was used as a catalyst are shown in C in Figure 3. And the measurement results when Pt-NPs (2) was used as a catalyst are shown in D in Figure 3.

[0069] Incidentally, the amount of hydrogen gas (H2(g)) generated by hydrolysis of ammonia borane (NH3BH3) using the above-mentioned tungsten carbide (WC-(Co0.92-Fe0.08) carbide) of this embodiment and Pt-NPs (Ball), Pt-NPs (1), and Pt-NPs (2) as comparative examples was evaluated by standardizing it to the mass of hydrogen product per specific surface area of ​​each catalyst. That is, for Pt-NPs (Ball), Pt-NPs (1), and Pt-NPs (2), it was evaluated as the mass of hydrogen product per specific surface area of ​​platinum (Pt) nanoparticles supported on alumina nanoparticles.

[0070] First, considering reusability, the amount of hydrogen gas (H2(g)) generated was compared when WC-(Co0.92-Fe0.08) carbide, Pt-NPs (Ball), and Pt-NPs (1) were used as catalysts. As shown in Figure 3, the amount of hydrogen gas (H2(g)) generated when using WC-(Co0.92-Fe0.08) carbide in this example was nearly three times the amount of hydrogen gas (H2(g)) generated when using Pt-NPs (Ball) and Pt-NPs (1).

[0071] Next, when comparing the amount of hydrogen (H2) gas generated when the WC-(Co0.92-Fe0.08) carbide of this embodiment and Pt-NPs (2) made by finely crushing granular Pt-NPs (Ball) were used as a catalyst each time, as shown in FIG. 3, the initial gas generation rate slope was the same, but the amount of hydrogen gas (H2 (g)) generated when WC-(Co0.92-Fe0.08) carbide was used after 40 minutes was about 2.5 times that of Pt-NPs (2).

[0072] From the above, it is recognized that the WC-(Co0.92-Fe0.08) carbide of this example is superior as a catalyst to platinum (Pt)-based noble metals.

[0073] The change over time in the amount of hydrogen gas (H2(g)) generated by hydrolysis of ammonia borane (NH3BH3) was confirmed using the tungsten carbide (WC-(Co0.92-Fe0.08) carbide) of this example and Pt-NPs (Ball), Pt-NPs (1), and Pt-NPs (2) given as comparative examples as catalysts.

[0074] Here, we define the entropy production (Sirr) and entropy rate (dSirr / dt) in the hydrolysis reaction of ammonia borane (NH3BH3) shown in the above-mentioned equation (1).

[0075] The entropy production (Sirr) represents the entropy of hydrogen gas (H2(g)) produced from ammonia borane (NH3BH3) through an irreversible process. The entropy rate (dSirr / dt) is the entropy production (Sirr) differentiated with respect to time (t).

[0076] From the relationship between the amount of hydrogen (H2) gas produced by the hydrolysis of ammonia borane (NH3BH3) and the stoichiometric coefficient, the amount of NH4 produced by the hydrolysis reaction of ammonia borane (NH3BH3) shown in equation (1) can be calculated. + (aq) and BO2 - The change in the number of moles of (aq) with time was calculated and converted into the change in the mass molar concentration b with time.

[0077] Next, the ionic strength I was evaluated using the following formula (2). m was evaluated.

[0078] JPEG0007659754000002.jpg1757

[0079] Here, z i is the valence of the ion, and b ° is the standard molality (b ° = 1 mol kg -1 ). Next, in order to evaluate the activity of the ionic species generated by the hydrolysis of ammonia borane (NH3BH3), the activity coefficient was evaluated using the Davies equation shown in the following formula (3). The applicable range of the Davies equation is 0.01 < I < 0.3. As shown in the calculation results of the ionic strength shown later, the hydrogen evolution reaction (HER) by the hydrolysis of ammonia borane (NH3BH3) described here is within the applicable range of the Davies equation.

[0080] JPEG0007659754000003.jpg17110

[0081] Next, the activity of each ionic species was evaluated from the values of the activity coefficient and the molality, and is shown in the following formula (4). The affinity A was evaluated according to the definition of affinity.

[0082] JPEG0007659754000004.jpg59115(4)

[0083] Here, Δ r G ° and p H2 are the standard reaction Gibbs energy of the hydrogen evolution reaction (HER) and the partial pressure of hydrogen, respectively. The partial pressure of hydrogen is 1.01325 bar. That is, up to the hydrogen recovery section in the hydrolysis device was regarded as the system for hydrogen generation.

[0084] The thermochemical equations for the hydrogen production reaction from the hydrolysis of ammonia borane (NH3BH3(cr)) at 298.15 K are shown in the following equations (I) to (VI).

[0085] Table 1 also lists ammonia borane (NH3BH3(cr)), ammonia (NH3(aq)), orthoboric acid (B(OH)3(aq)), ammonium (NH4 + (aq) ), metaboric acid (BO2(aq)), H2O(l) 、 Thermodynamic quantities at 298.15 K for standard substances of N2(g) and B(cr) are shown.

[0086] The standard enthalpy of formation of ammonia borane (NH3BH3(cr)) (Δ f H ° m ) and third law entropy (S ° m ) adopted the measurement results of Shaulov et al. and Wolf et al. The standard entropy of formation (Δ f S ° m ) to calculate the third law entropy (S ° m ) and the standard enthalpy of formation (Δ f H ° m ) and the standard Gibbs energy of formation (Δ f G ° m =-59.615±5.864 (kJ mol -1 )) was adopted. In addition, H2O(l), ammonia (NH3(aq)), orthoboric acid (B(OH)3(aq)), ammonium (NH4 + (aq), the standard Gibbs energy of metaboric acid (BO2(aq)) (Δ f G ° m ) cited values ​​from a data book.

[0087] The following formula (I) is the hydration reaction of ammonia borane (NH3BH3(aq)) whose thermodynamic values ​​are unknown, and its thermochemical quantities are also unknown. The following formula (II) is the hydrogen production reaction (HER) by hydrolysis of ammonia borane (NH3BH3(cr)). The sum of formulas (I) and (II) can be rewritten as the following formula (III). Formula (IV) is the reaction of ammonium (NH4 + Equation (V) shows the production of metaboric acid (BO2(aq)). Equation (VI) is rewritten as the sum of these reactions, with the left side showing the initial state and the right side showing the final state.

[0088] JPEG0007659754000005.jpg88154

[0089] The standard reaction Gibbs energy thus obtained (Δ f G ° m ) was used, and the temperature of the system was considered to be approximately constant at 25°C (298.15K).

[0090] The change in thermodynamic force A / T over time was evaluated by dividing the determined affinity A by the temperature.

[0091] The production of hydrogen gas (H2) from ammonia borane (NH3BH3) through hydrolysis is an irreversible process, and entropy is generated within the system during the production. This is defined as the entropy production Sirr. The entropy rate (dSirr / dt) is the derivative of the entropy production (Sirr) with respect to time (t). The entropy rate (dSirr / dt) was defined by the following equation (5).

[0092] dSirr / dt=(A / T)(dξ / dt) ···(5) Here, A is the affinity and ξ indicates the degree of reaction progress.

[0093] The enthalpy production (Sirr) was determined by integrating the entropy rate (dSirr / dt) obtained from equation (5) above.

[0094] Table 1 Thermodynamic quantities used to determine entropy production and their errors U. JPEG0007659754000006.jpg92168

[0095] FIG. 4 shows the time differential (dSirr / dt) of the entropy production of the irreversible process in the hydrogen production reaction produced by hydrolysis of ammonia borane (NH3BH3) using the tungsten carbide (WC-(Co0.92-Fe0.08) carbide) of this embodiment and Pt-NPs (Ball), Pt-NPs (1), and Pt-NPs (2) as comparative examples as catalysts.

[0096] In FIG. 4, A shows the change in entropy generation over time when the tungsten carbide (WC-(Co0.92-Fe0.08) carbide) of this embodiment is used as a catalyst, B shows the change in entropy generation over time when Pt-NPs (Ball) is used as a catalyst, C shows the change in entropy generation over time when Pt-NPs (1) is used as a catalyst, and D shows the change in entropy generation over time when Pt-NPs (2) is used as a catalyst.

[0097] As shown in Figure 4, the entropy generation rate (dSirr / dt) when hydrogen was generated using the tungsten carbide (WC-(Co0.92-Fe0.08) carbide) of this example and Pt-NPs (2) as catalysts decreased gradually over time. In contrast, the entropy generation rate (dSirr / dt) when Pt-NPs (Ball) and Pt-NPs (1) were used as catalysts decreased with oscillation.

[0098] FIG. 5 shows the second-order time derivative (d 2 Sirr / dt 2) over time is shown in A. Figure 6 shows the second-order time derivative (d 2 Sirr / dt 2 6 shows the time-dependent change in the electrochemical properties of Pt-NPs (ball), Pt-NPs (1), and Pt-NPs (2).

[0099] The second-order time differential (d 2 Sirr / dt 2 ) decayed smoothly over time. In contrast, the Pt-NPs (2), whose first-order time derivative (dSirr / dt) was smooth over time, showed a smooth change in the second-order time derivative (d 2 Sirr / dt 2 ) over time, it oscillated as shown in Figure 6D. The second-order time derivative (d 2 Sirr / dt 2 ) As shown in Fig. 6B and C, the time-dependent change in the SiR amplitude showed oscillations similar to those in the first-order time derivative (dSirr / dt).

[0100] Furthermore, the mechanism by which ammonia borane (NH3BH3) is hydrolyzed to generate hydrogen (H2) using the tungsten carbide (WC-(Co0.92-Fe0.08) carbide) of this embodiment as a catalyst will be described in more detail with reference to FIG. 1.

[0101] Tungsten carbide (WC) that constitutes the tungsten carbide (WC-(Co0.92-Fe0.08) carbide) of this embodiment can be said to be a platinum (Pt)-like substance that has a structure similar to platinum (Pt) in terms of the arrangement of electrons. WC, which is a platinum (Pt)-like substance, has a strong affinity with ammonia borane (NH3BH3) and brings it closer.

[0102] Tungsten carbide (WC) brings ammonia borane (NH3BH3) close and simultaneously coordinates the B component in ammonia borane (NH3BH3). This is because of the strong attractive interaction between the W component in tungsten carbide (WC) and the B component in ammonia borane (NH3BH3).

[0103] When the B component in ammonia borane (NH3BH3) coordinates with the W of tungsten carbide (WC), ammonia borane (NH3BH3) begins to decompose into NH3(aq) and BH3(aq).

[0104] The unstable molecule BH3(aq) decomposes, and by reaching equilibrium, the three OH atoms in the three surrounding water molecules (H2O(l)) are released. - ions to form B(OH)3(aq), while at the same time releasing three H + (aq) i.e., release a proton.

[0105] Here, three OH - The three water molecules (H2O(l)) that release (aq) also release three protons.

[0106] The six protons released from both BH3(aq) and water molecules (H2O(l)) each have a nuclear spin. These protons with nuclear spin interact with the electron spins of the cobalt-iron (Co-Fe) alloy nanocrystals dissolved in the WC framework through dipole-dipole interactions, and are assembled and aligned on the surface.

[0107] BH3(aq) produced by decomposing ammonia borane (NH3BH3) releases three protons and discharges three electrons. Three OH(aq) released from three water molecules (H2O(l)) also discharge three electrons. These six discharged electrons are transferred to the Co-Fe alloy nanocrystals via the W atoms in the WC skeleton.

[0108] The six electrons transferred to the Co-Fe alloy nanocrystal reduce the protons collectively arranged on the surface of the Co-Fe alloy nanocrystal, generating six atomic radical hydrogen atoms (H).

[0109] Finally, three hydrogen molecules (H2) are produced from six radical hydrogen atoms (H). In Figure 1, due to space limitations, the process is illustrated in which one proton is released from one BH3(aq) and one proton is released from one H2O(l), resulting in the release of two protons from each of the above-mentioned cycles.

[0110] Furthermore, the mechanism by which the generated hydrogen molecules (H2) are desorbed as gaseous hydrogen gas (H2(g)) will be described with reference to FIG. 7. In FIG. 7, when ammonia borane (NH3BH3) is hydrolyzed using the tungsten carbide (WC-(Co0.92-Fe0.08) carbide) of this embodiment as a catalyst, the hydrogen gas (H2(g)) generated on the surface of the Co0.92-Fe0.08 alloy nanocrystals solid-dissolved in the lattice of WC is diamagnetic, and is magnetized in the opposite direction to the magnetic field of the ferromagnetic Co0.92-Fe0.08. As a result, a magnetic repulsive interaction occurs between the two, and the hydrogen gas (H2(g)) is easily desorbed from the surface of the ferromagnetic Co0.92-Fe0.08 alloy nanocrystals.

[0111] That is, in the case of WC-(Co0.92-Fe0.08) carbide, the protons (H + ) to the surface of the ferromagnetic Co0.92-Fe0.08 alloy nanocrystals by magnetic dipole action, followed by the release of protons (H + The pathway of the hydrogen evolution reaction (HER) is consistent from the accumulation and reduction of hydrogen molecules (H2) to the desorption of the generated hydrogen molecules (H2) due to diamagnetism. Therefore, by hydrolyzing ammonia borane (NH3BH3) using the WC-(Co0.92-Fe0.08) carbide of this embodiment as a catalyst, the entropy production rate (dSirr / dt) and the time derivative of the entropy production rate (dSirr / dt) in the hydrogen evolution reaction (HER) described above are 2 Sirr / dt2 ) changes smoothly over time. Therefore, by using the WC-(Co0.92-Fe0.08) carbide of this embodiment as a catalyst for hydrolysis of ammonia borane (NH3BH3), it is possible to generate hydrogen (H2) while maintaining a stable release rate.

[0112] Here, for comparison with the tungsten carbide according to the present invention, the mechanism when ammonia borane (NH3BH3) is hydrolyzed using platinum (Pt) as a catalyst will be described with reference to FIG.

[0113] When platinum (Pt) is used as a catalyst in the hydrolysis of ammonia borane (NH3BH3) to produce hydrogen (H2), a sequential exchange of ammonia borane (NH3BH3) adsorption sites and hydrogen production sites occurs.

[0114] Incidentally, platinum (Pt) nanoparticles are one of the elements that have a large heat of adsorption of hydrogen gas (H2(g)). Therefore, hydrogen gas (H2(g)) is energetically stable when adsorbed on the surface of platinum (Pt) nanoparticles, as shown in (a) of Figure 8, and it is difficult for hydrogen gas (H2(g)) to immediately desorb from the surface of platinum (Pt) nanoparticles.

[0115] From this, hydrogen (H2(g)) molecules generated from ammonia borane (NH3BH3) gather on the surface of platinum (Pt) nanoparticles, as shown in (b) of Figure 8. Then, it is thought that the gathered hydrogen molecules (H2) intermittently become bubbles of hydrogen gas (H2(g)) and are released from those that have gained enough buoyancy to be able to detach from the surface of the platinum (Pt) nanoparticles, as shown in (c) of Figure 8.

[0116] Thus, when platinum (Pt) is used as a catalyst, the entropy production rate (dSirr / dt) and the time derivative of the entropy production rate (dSirr / dt) in the hydrogen evolution reaction (HER) are 2 Sirr / dt 2) changes over time, as shown in Figures 5 and 6, causing vibrations, making it difficult to generate hydrogen stably and smoothly over time, as in the case of using the tungsten carbide of this embodiment. [Industrial Applicability]

[0117] The tungsten carbide containing a Co-WC solid solution used as the hydrogen production catalyst according to the present invention is hydrophilic, and is therefore useful as a catalyst when ammonia borane (NH3BH3) is mixed and dissolved in pure water to cause hydrolysis.

[0118] Furthermore, the tungsten carbide constituting the hydrogen production catalyst according to the present invention is useful as a cathode electrode material for hydrogen production by water electrolysis.

Claims

1. Ammonia borane (NH 3 BH 3 ) to hydrogen (H 2 A catalyst for producing hydrogen used to produce hydrogen, comprising: A catalyst for producing hydrogen, comprising ferromagnetic tungsten carbide having ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals dissolved in a tungsten carbide (WC) lattice and having an internal magnetic field applied thereto.

2. The catalyst for producing hydrogen according to claim 1, characterized in that the tungsten carbide encapsulates cobalt-iron (Co-Fe) alloy nanocrystals composed of 99.5 to 91.5 mol % of ferromagnetic cobalt (Co) and 0.5 to 8.5 mol % of iron (Fe) to provide an internal magnetic field.

3. Ammonia borane (NH 3 BH 3 A method for producing a hydrogen production catalyst made of tungsten carbide, which is used to produce hydrogen from a tungsten alloy comprising the steps of: A mixed aqueous solution is prepared by mixing a tungsten component with a ferromagnetic cobalt component and an iron component; Next, the mixed aqueous solution is evaporated to dryness or spray-dried to produce a solid material containing a cobalt component and an iron component; The solid is thermally decomposed to produce an oxide powder, which is then subjected to hydrogen thermal reduction to produce a cobalt-iron (Co-Fe) alloy solid solution tungsten alloy powder; Thereafter, the cobalt-iron (Co-Fe) alloy solid solution tungsten alloy powder was carbonized to produce tungsten carbide containing ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals and having an internal magnetic field applied thereto to make it ferromagnetic. A method for producing a catalyst for producing hydrogen, comprising:

4. In the step of carbonizing the cobalt-iron (Co-Fe) alloy solid solution tungsten alloy powder, a tungsten composite carbide (W 6 (Co-Fe) 6 C, (Co-Fe) 2 W 4 4. The method for producing a catalyst for producing hydrogen according to claim 3, wherein

5. 5. The method for producing a catalyst for hydrogen production according to claim 3, wherein the mixed aqueous solution is a mixture of a cobalt-iron (Co-Fe) alloy component, in which cobalt (Co) is mixed at a ratio of 99.5 to 91.5 mol % and iron (Fe) is mixed at a ratio of 0.5 to 8.5 mol %, and a tungsten component is mixed at a molar ratio of 20:

80.

6. The hydrogen production catalyst according to claim 1 or 2 and ammonia borane (NH 3 BH 3 ) is mixed with the aqueous solution, and the aqueous solution is then hydrolyzed to obtain the ammonia borane (NH 3 BH 3 ) to hydrogen gas (H 2 (g) is a hydrogen production method.

7. The aqueous solution is hydrolyzed to produce ammonia borane (NH 3 BH 3 When hydrogen gas is generated from hydrogen, diamagnetic hydrogen gas (H 2 (g)) and the ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals, the hydrogen gas (H 2 The method for producing hydrogen according to claim 6, further comprising the step of: (g) removing the cobalt-iron (Co-Fe) alloy nanocrystals from the surface of the nanocrystals.

8. A catalyst for producing hydrogen produced by the production method according to claim 3 or 4 and ammonia borane (NH 3 BH 3 ) is mixed with the aqueous solution, and the aqueous solution is then hydrolyzed to obtain the ammonia borane (NH 3 BH 3 ) to hydrogen gas (H 2 (g) is a hydrogen production method.

9. A method for producing hydrogen, comprising preparing an aqueous solution by mixing a hydrogen production catalyst produced by the production method described in claim 5 with ammonia borane (NH 3 BH 3 ), then hydrolyzing the aqueous solution to generate hydrogen gas (H 2 (g)) from the ammonia borane (NH 3 BH 3 ).

10. The aqueous solution is hydrolyzed to produce ammonia borane (NH 3 BH 3 ) to hydrogen gas (H 2 When the hydrogen gas (H(g)) is generated, the hydrogen gas (H(g)) is generated by the repulsive interaction between the diamagnetic hydrogen gas and the ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals. 2 9. The method for producing hydrogen according to claim 8, further comprising the step of: (g) removing the cobalt-iron (Co-Fe) alloy nanocrystals from their surfaces.

11. The method for producing hydrogen as described in claim 9, characterized in that when the aqueous solution is hydrolyzed to generate hydrogen gas (H2(g)) from the ammonia borane (NH3BH3), the hydrogen gas (H2(g)) is desorbed from the surface of the cobalt-iron (Co-Fe) alloy nanocrystals due to repulsive interaction between the diamagnetic hydrogen gas and the ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals.

12. The hydrogen production catalyst according to claim 1 or 2 and ammonia borane (NH 3 BH 3 ) to prepare an aqueous solution, Next, the aqueous solution is hydrolyzed to form the ammonia borane (NH 3 BH 3 ) is adsorbed and cleaved to produce protons (H + ) is released, The proton (H + The protons (H ) are transferred to the surface of the ferromagnetic cobalt-iron (Co—Fe) alloy nanocrystals in the hydrogen production catalyst by the magnetic dipole action between the protons (H ) and the electron spins from the cobalt-iron (Co—Fe) alloy in the hydrogen production catalyst. + ) and reduce it to diamagnetic hydrogen molecules (H 2 ) The ferromagnetic cobalt-iron (Co—Fe) alloy nanocrystals and the diamagnetic hydrogen molecules (H 2 ) due to the magnetic repulsive interaction, the time derivative (dSirr / dt) of the entropy generation rate of the irreversible process 2 Sirr / dt 2 The hydrogen molecules (H ) are prevented from oscillating unstably over time, and the hydrogen molecules (H ) are released from the surface of the cobalt-iron (Co—Fe) alloy nanocrystals. 2 ) to generate hydrogen gas.

13. A catalyst for hydrogen production produced by the production method according to claim 3 or 4 and ammonia borane (NH 3 BH 3 ) to prepare an aqueous solution, Next, the aqueous solution is hydrolyzed to form the ammonia borane (NH 3 BH 3 ) is adsorbed and cleaved to produce protons (H + ) is released, The proton (H + The protons (H ) are transferred to the surface of the ferromagnetic cobalt-iron (Co—Fe) alloy nanocrystals in the hydrogen production catalyst by the magnetic dipole action between the protons (H ) and the electron spins from the cobalt-iron (Co—Fe) alloy nanocrystals in the hydrogen production catalyst. + ) and reduce it to diamagnetic hydrogen molecules (H 2 ) The ferromagnetic cobalt-iron (Co—Fe) alloy nanocrystals and the diamagnetic hydrogen molecules (H 2 ) due to the magnetic repulsive interaction, the time derivative (dSirr / dt) of the entropy generation rate of the irreversible process 2 Sirr / dt 2 ) from the surface of the cobalt-iron (Co-Fe) alloy nanocrystals. 2 ) to generate hydrogen gas.

14. A method for producing hydrogen by the method according to claim 5, comprising the steps of: preparing an aqueous solution by mixing ammonia borane (NH 3 BH 3 ) with the catalyst for producing hydrogen produced by the method according to claim 5; Next, the aqueous solution is hydrolyzed to cause the ammonia borane (NH 3 BH 3 ) to be adsorbed on the tungsten carbide (WC) surface in the hydrogen production catalyst and then cleaved to release protons (H + ); The protons (H + ) are accumulated on the surface of the ferromagnetic cobalt-iron (Co—Fe) alloy nanocrystals in the hydrogen production catalyst due to a magnetic dipole action between the protons (H + ) and the electron spins from the cobalt-iron (Co—Fe) alloy nanocrystals in the hydrogen production catalyst, and are reduced to generate diamagnetic hydrogen molecules (H 2 ); The magnetic properties of the ferromagnetic cobalt-iron (Co-Fe) alloy nanocrystals and the diamagnetic hydrogen molecules (H 2 ) The method for producing hydrogen is characterized in that the hydrogen molecules (H 2 ) are desorbed from the surface of the cobalt-iron (Co—Fe) alloy nanocrystals to generate hydrogen gas by suppressing the unstable oscillation of the time derivative (d 2 Sirr / dt 2 ) of the entropy generation rate (dSirr / dt) of the irreversible process due to mutual repulsive interactions.

Citation Information

Patent Citations

  • Direct type fuel cell

    JP2006286549A

  • Fuel cell

    JP2009176556A

  • Powder of tungsten alloy with transition metal dissolved therein as solid solution and process for producing the same

    JP2010077524A

  • Catalyst for hydrogen production and method for producing the same, and method for hydrogen production

    JP2019098328A

  • Catalyst for hydrogen production

    JP2023061564A